Cultural Values, Corruption Level and Earnings Management: Evidence of South East Asia Countries - Putra, Andi Manggala (2016)
Agency theory predicts that principal incurs cost to bring alignment of interest between shareholders and managers. This is inevitable because principal-agent conflict exists through problems of contractual interpretation. Agents’ incentive will be parallel with principals’ only if agents believe that the contract is correctly interpreted. However, such cost is not only affected by contractual agreement. The legal mechanism, investor protection, political environment, culture, and other social constructs and values are also factors that affect the principal-agent relationship. This study scrutinises the correlation between earnings quality and agency cost based on corruption level of Transparency International and cultural values of Hofstede Centre in six South-East Asian (SEA) countries: Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam. I restrict categorisation of each SEA country to whether they have low or high agency cost based on average value of agency score. Moreover, I also study whether high (low) agency cost level is correlated with conservative (aggressive) abnormal accruals as the second phase of analysis. This study employs 581 firm-years observations from the 30 biggest market capitalisation firms of six SEA countries. I run multiple regressions of three main accrual models for main analysis (Jones, 1991; Dechow, et al., 1995; Kasznik, 1999) and two alternative accrual models for sensitivity analysis (Dechow, et al., 2002; Dechow & Dichev, 2002) to get discretionary accruals. I employ univariate and regression analyses to find the correlation between high agency cost specific-country measure and discretionary accruals. I run linear regressions of country agency cost level dummy and control variables of size, leverage ratio, book-to-market ratio on discretionary accruals. In the second phase of this study, I split firm-year observations which have positive (negative) abnormal accruals as firms conducting aggressive (conservative) earnings management. Then, I run linear regressions of country agency cost level dummy and control variables of size, leverage ratio, book-to-market ratio on aggressive/conservative discretionary accruals. Results show that firms in low agency cost countries have lower earnings quality, and indicate that earnings management behaviour in this study is efficient rather than detrimental. The results also indicate that mechanisms of corporate governance (not specifically identified in this study) have successfully been developed to inhibit earnings discretion behaviour. In the second phase of analysis, results present that firms in low agency countries conduct more aggressive and conservative earnings management than their counterparts in high agency countries. Furthermore, results present that firms with bigger size engage less in earnings management conduct (either income-increasing or decreasing) compared to their counterparts. Scrutinising media and analysts cause fewer incentives for managers to perform earnings management. Also, results show that book-to-market (leverage) is negatively (positively) correlated with conservative accounting. This indicates that firms with growing expectation have less abnormal accruals. Also, it depicts that firms avoid reducing earnings because firms with high leverage can suffer from financial distress that could lead to contractual renegotiations (Becker, et al., 1998). Overall, based on all evidence it is conclusive that earnings management in six SEA countries is indeed beneficial rather than detrimental. Both aggressive and conservative earnings management are means of accounting manipulation engaged in by management even when the agency cost is low. This contributes to existing literature on earnings management as a form of bias that favours both principal and agents (Jiraporn, et al., 2008; Siregar & Utama, 2008; Subramanyam, 1996). Also, I suspect that unidentified internal or external control mechanisms such as legal enforcement, accounting standard, typical investors in companies and other governance mechanism have been successfully applied, directly or indirectly, to constrain earnings management conduct (either in aggressive or conservative ways) in high agency cost countries.